2021
DOI: 10.3390/agronomy11030436
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nutrient Uptake, Growth, Yield and Protein Content in Chickpea by the Co-Addition of Phosphorus Fertilizers, Organic Manures, and Bacillus sp. MN-54

Abstract: The main purpose of this study was to examine the impact of different phosphorus (P) fertilizers and organic manures alone and in combination with Bacillus sp. MN-54 on growth, yield, nutrient uptake, chlorophyll (SPAD value) and crude proteins content of chickpea. The simple manure (SM), processed manure (PM), single super phosphate (SSP), and rock phosphate (RP) were applied individually and in different combinations to the soil in pots, and the chickpea seeds treated with Bacillus sp. MN-54 were sown in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 60 publications
5
15
0
2
Order By: Relevance
“…Number of nodules plant -1 was significantly increased owing to combined application of chemical fertilizers@ half potency, organic input and biofertilizer. Similar results were observed by Khan et al [22] under chickpea crop.…”
Section: Resultssupporting
confidence: 90%
“…Number of nodules plant -1 was significantly increased owing to combined application of chemical fertilizers@ half potency, organic input and biofertilizer. Similar results were observed by Khan et al [22] under chickpea crop.…”
Section: Resultssupporting
confidence: 90%
“…MN-54 has been used to improve P uptake and growth of maize under lead [47] and chromium [48] toxicity. Similarly, Khan et al [44] reported that Bacillus spp. MN-54 improved P uptake and enhanced chickpea productivity in calcareous soils.…”
Section: Introductionmentioning
confidence: 90%
“…Plant growth promoting microorganisms are being exploited in the recent era to avoid the negative impacts of synthetic fertilizers [44]. The ability of these microorganism to improve plant minerals' uptake has been witnessed in the recent decade [45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MN54, previously identified from the maize rhizosphere and characterized as hydrocarbons degrader and plant growth promoter was taken from the Soil and Environmental Microbiology Lab of ISES, UAF [23,43]. The strain also has ability to improve plant growth in various crops under normal or stressed environment as presented in Figure S1 [23,44]. The Bacillus sp.…”
Section: Experimental Layoutmentioning
confidence: 99%